Natural disasters through infographics - Higgins, Nadia; Sciuto, Alex (Minneapolis Lerner Publications, 2014)
This book displays Earth's systems, their interactions, and those impacts on populations, including earthquakes and volcanoes caused by shifting plates, atmospheric changes, and other natural events
Includes index
Marsa
5 17 18 21 22
Keywords: Natural disasters -- Juvenile literature